Macrophage-Regulatory T Cell Interactions Promote Type 2 Immune Homeostasis Through Resistin-Like Molecule α - Li, Jiang; Kim, Sang Yong; Lainez, Nancy M.; Coss, Djurdjica; Nair, Meera G. (Frontiers in Immunology, 2021)
RELMα is a small, secreted protein expressed by type 2 cytokine-activated “M2” macrophages in helminth infection and allergy. At steady state and in response to type 2 cytokines, RELMα is highly expressed by peritoneal macrophages, however, its function in the serosal cavity is unclear. In this study, we generated RELMα TdTomato (Td) reporter/knockout (RαTd) mice and investigated RELMα function in IL-4 complex (IL-4c)-induced peritoneal inflammation. We first validated the RELMαTd/Td transgenic mice and showed that IL-4c injection led to the significant expansion of large peritoneal macrophages that expressed Td but not RELMα protein, while RELMα+/+ mice expressed RELMα and not Td. Functionally, RELMαTd/Td mice had increased IL-4 induced peritoneal macrophage responses and splenomegaly compared to RELMα+/+ mice. Gene expression analysis indicated that RELMαTd/Td peritoneal macrophages were more proliferative and activated than RELMα+/+ macrophages, with increased genes associated with T cell responses, growth factor and cytokine signaling, but decreased genes associated with differentiation and maintenance of myeloid cells. We tested the hypothesis that RαTd/Td macrophages drive aberrant T cell activation using peritoneal macrophage and T cell co-culture. There were no differences in CD4+ T cell effector responses when co-cultured with RELMα+/+ or RELMαTd/Td macrophages, however, RELMαTd/Td macrophages were impaired in their ability to sustain proliferation of FoxP3+ regulatory T cells (Treg). Supportive of the in vitro results, immunofluorescent staining of the spleens revealed significantly decreased FoxP3+ cells in the RELMαTd/Td spleens compared to RELMα+/+ spleens. Taken together, these studies identify a new RELMα regulatory pathway whereby RELMα-expressing macrophages directly sustain Treg proliferation to limit type 2 inflammatory responses.